PERBEDAAN TINGKAT KECUKUPAN ZAT GIZI DAN RIWAYAT PEMBERIAN ASI EKSKLUSIF PADA BALITA STUNTING DAN NON STUNTING - Retty Anisa Damayanti; Lailatul Muniroh; Farapti Farapti (Universitas Airlangga, 2016)
Stunting is an accumulative process of inadequacy number of nutrients in a long period of time. The purpose of this research was to analyse the difference of nutrients adequacy and the history of exclusive breastfeeding between stunting and non stunting toddler. This cross sectional research was done in 113 toddler who is categorized to 27 stunting toddler and 86 non stunting toddler at Kejawan Putih Tambak village, Surabaya. The number of sample was calculated with proportional sampling. To compare the nutrients adequacy and the history of exclusive breastfeeding,Chi-square test and Exact Fisher were used, to compare amount of intake, Independent T-test and Odds Ratio were calculated. As a result, there was a difference in energy, protein, zinc and iron consumption, and there was also a difference in history of exclusive breastfeeding between stunting and non-stunting toddler (p = 0.000), Non stunting toddler have a higher intake of energy, protein, zinc, and iron than stunting toddler. Toddler with non exclusive breastfeeding have a higher risk to be stunting than toddler with exclusive breastfeeding, and toddler who have inadequate energy, protein, zinc, and iron intake have a higher risk to be stunting than toddler with adequate energy, protein, zinc and iron intake (non-exclusive breastfeeding = 16.5 times, inadequate energy = 4.84 times, inadequateprotein = 3.4 times, inadequate zinc = 3.72 times, inadequate iron = 2.36 times). Advice that can be given is that mother should increase food intake of toddler, especially food that contain protein, zinc, and iron and mother should give also more attention to the exclusive breastfeeding and complementary feeding which is suitable with the toddler’s age.Keywords: exclusive breastfeeding, toddler, stunting, nutrient adequacy